1972
DOI: 10.1103/physrevd.5.1992
|View full text |Cite
|
Sign up to set email alerts
|

Efimov's Effect: A New Pathology of Three-Particle Systems. II

Abstract: By studying the eigenvalue spectrum of the Faddeev kernel in a certain singular limit, we give an independent proof of an effect recently deduced by Efimov: When three identical particles interact via short-range pairwise potentials, the number of three-body bound states grows without limit when the pairwise scattering length a becomes large. [ The number of bound states is then roughly (l/~r)ln(A la I), where A is a momentum cutoff]. We extend our proof to the case where only two particles are identical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0
9

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 4 publications
8
91
0
9
Order By: Relevance
“…Это соотношение верно, если ε = J/(48c − 5), где c = T 3 ds 1 ds 2 ds 3 9 + cos s 1 + cos s 2 + cos s 3 .…”
Section: двухмагнонное состояниеunclassified
See 1 more Smart Citation
“…Это соотношение верно, если ε = J/(48c − 5), где c = T 3 ds 1 ds 2 ds 3 9 + cos s 1 + cos s 2 + cos s 3 .…”
Section: двухмагнонное состояниеunclassified
“…Этот эффект впервые был обнаружен Ефимовым [1]. В работах [2], [3] эта задача изучалась в физическом аспекте. Строгое математическое доказательство существования эффекта Ефимова было проведено впервые в работе [4], а затем в работах [5]- [7].…”
Section: Introductionunclassified
“…As discussed in Ref. [7] this occurs not only for identical particles, a situation first considered by Efimov [8][9][10], but also for two identical and one different particle. In particular, in the case of two heavy particles and one light particle these authors found that the heavyheavy interaction does not matter, and there is an infinite number of bound trimer states as long as the light-heavy scattering length becomes infinite.…”
mentioning
confidence: 95%
“…The authors thank Dr. M. Bhattacharya for helpful discussions, and Dr. P. Julienne for bringing Ref. [7] to their attention. * Electronic address: pierre.meystre@optics.arizona.edu…”
mentioning
confidence: 99%
“…We can find the domain equation by combining (12) and (13). Together, as Λ → ∞, these equations impose the following conditions on wavefunctions:…”
Section: Renormalizing the Three-body Problemmentioning
confidence: 99%